2020
DOI: 10.3390/cells9010170
|View full text |Cite
|
Sign up to set email alerts
|

RK-33 Is a Broad-Spectrum Antiviral Agent That Targets DEAD-Box RNA Helicase DDX3X

Abstract: Viral disease is one of the greatest burdens for human health worldwide, with an urgent need for efficacious antiviral strategies. While antiviral drugs are available, in many cases, they are prone to the development of drug resistance. A way to overcome drug resistance associated with common antiviral therapies is to develop antivirals targeting host cellular co-factors critical to viral replication, such as DEAD-box helicase 3 X-linked (DDX3X), which plays key roles in RNA metabolism and the antiviral respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…Prompted by these results, we assessed if DDX3X is required for SARS-CoV-2 infection by using two specific inhibitors of DDX3X, the diazepine derivative RK-33 ( Yang et al, 2020 ) and the rhodanine Compound 4B (C-4B) ( Maga et al, 2011 ) ( Figure 4 A). Vero E6 cells were infected with SARS-CoV-2 at MOI 0.001 for 1 hour followed by incubation with the RK-33 or C-4B compounds for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Prompted by these results, we assessed if DDX3X is required for SARS-CoV-2 infection by using two specific inhibitors of DDX3X, the diazepine derivative RK-33 ( Yang et al, 2020 ) and the rhodanine Compound 4B (C-4B) ( Maga et al, 2011 ) ( Figure 4 A). Vero E6 cells were infected with SARS-CoV-2 at MOI 0.001 for 1 hour followed by incubation with the RK-33 or C-4B compounds for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, during the late stages of infection, DENV down-regulates DDX3 expression to facilitate viral replication [75]. However, treatment with the DDX3 inhibitor RK-33 reduces DENV replication, suggesting that DDX3 promotes viral replication [76,77]. Furthermore, some evidence showed that DDX3 interacts with the calcium channel TRPV4 to facilitate viral replication of DENV and ZIKV [78].…”
Section: Flaviviruses and Hepacivirusmentioning
confidence: 99%
“…Two inhibitors of DDX3X have recently been reported [171,172]. RK-33 is a ring-expanded nucleoside that directly interacts with DDX3X and inhibits its ATPase and helicase activity.…”
Section: Targeting Ddx/dhx-box Helicases In Translation Initiationmentioning
confidence: 99%